RHETORICAL STRATEGIES BY GOVERNOR CANDIDATES IN THE JAKARTA ELECTORAL DEBATE 2017RHETORICAL STRATEGIES BY GOVERNOR CANDIDATES IN THE JAKARTA ELECTORAL DEBATE 2017 - Suwandonadi Simanullang; Amrin Saragih; Rahmad Husein (State University of Medan, 2019)
This study deals with rhetorical strategies used by governor candidates in the Jakarta Electoral Debate 2017. The aims of this study are to (1) describe rhetorical strategies which are used by governor candidates in the Jakarta Electoral Debate 2017, (2) analyze the realizations of rhetorical strategies, (3) reason the use of rhetorical strategies. This study was conducted by using descriptive qualitative research. The source of data was the Jakarta Electoral Debate 2017. The data were collected by using documentary technique. Instrument for collecting the data was the documentary sheet. The results of the study show that the three rhetorical strategies, i.e. Logos, Ethos, Pathos, are found in the debates. The three realizations of rhetorical strategies are also found in the debates. Reasons for using rhetorical strategies are to acclaim, to attack, and to defend. Keywords: Rhetorical Strategies, Governor Candidates, Jakarta Electoral Debate